TOURISM RESEARCH IN SPAIN: THE STATE OF THE ART - Alfonso Vargas-Sánchez (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 1970)
This paper analyses the evolution that Tourism Research has undergone in Spain in the last few years as well as its present situation, on the basis of four different variables: (i) the PhD dissertations carried out in the last ten years; (ii) the papers published in any ISI source during the last five years; (iii) the scientific journals on Tourism edited in Spain; (iv) and finally, the active research groups, centres and networks concerned with Tourism that exist in the country at the moment. In general terms, it will be shown that, despite becoming more and more multidisciplinary and a subject mater of interest for a larger number of higher education institutions, the research carried out on Tourism in Spain seems to be still restricted to very few fields of knowledge, universities and regions.